A Rossetti Family Chronology - Chapman, A. author. aut Link
XXVII, 484 p.
Keywords: This book focuses on Christina and Dante Gabriel Rossetti, it demonstrates the interconnectedness of their friendships and creativity, giving information about literary composition and artistic output, publication and exhibition, and details literary and artistic influences. It draws on many unpublished sources, including letters and diaries.